Effect of number of utilizations in a barley grass in Mediterranean conditions on biomass production and the admissibe stocking rate of Majorcan red sheep - Jaume J.; Moya J.; Joy M.; Cifre J.; Rovira J.; Joy S. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Majorcan Red Sheep is an endangered sheep breed and its conservation depends on the availability of feed resources and its use for feeding them. Animal production is considered a multifunctional activity due to its implication in economic, ecological and social aspects, which are strongly linked to its sustainability. The Majorcan Red Sheep production system has been directly linked to the exploitation of agricultural production. There is a clear positive economic impact when forage resources are used appropriately. The aim of this study was to determine the effect of the number of uses (1 to 3) on the herbage production of a barley crop and to estimate the suitable stocking rate. Results from this study showed that increasing the number of usesfrom 1 to 3 allowed greater production of forage (1863 vs 3274 Kg DM/ha), crude protein (113 vs 528 kg CP/ha) and more energy (3546 vs 8047 Mcal ME/ha). Therefore the suitable stocking rate is greater when a forage barley crop is used 3 times.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)